Model reduction of linear dynamical systems with quaternionic symmetry - Pereira, Ricardo (2008)
Model reduction techniques permit to approximate a dynamical system by a simpler one. However, it is desirable that some characteristics of the system are not lost in this process. In this paper we present a model reduction algorithm that preserves the symmetry of linear dynamical systems with quaternionic symmetry.